P-233 The perspective of hospice care from people with multiple sclerosis, a qualitative research study. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Hodges, Emma; Read, Sue; Santatzoglou, Sotirios
Abstract : The research aimed to understand the lived experience of people living with multiple sclerosis (MS), their perspectives of hospice care and particularly the supportive care group at St Giles. St Giles runs three MS Groups which are based around exercise and wellbeing and as the attendees make a donation they are self-sustaining financially. As hospices consider their role in rehabilitative palliative care and for people with a palliative illness not in the last 12 months of life this study aims to contribute to strategic thinking. The groups are a model of service provision for people living with potentially long term palliative conditions. The research aimed to inform future service developments for people with MS in addition to other people who may benefit from this type of service. Whilst the service itself has been evaluated, exploring attendees' perspective in more depth and whether 'hospice' was a barrier to access hadn't been done. The research study in partnership with Keele University involved three focus groups with 20 people participating and the opportunity for follow up with a semi-structured interview, six interviews were undertaken. A thematic analysis was then completed. The results suggested that 'hospice' was an initial barrier for a small number of attendees, however for most the opportunity to exercise with other people with MS was the 'hook' that encouraged people to join the group. The results demonstrated the importance for attendees to be with other MS patients there was a theme of acceptance and shared understanding. There was a theme of insufficient information being available following diagnosis and a sense of 'being left to get on with it'. There was an incredible sense of resilience and community. There is learning that contributes to future service developments for other groups but also some additional support for the MS group that would add value.